Mars attacks!. - Nicholson, Jack.; Close, Glenn. 1947-; Bening, Annette (Burbank, CA : Warner Home Video, 1997)
Mean, green invaders from the angry red planet attempt to take over the earth.
For specific features see interactive menu./ Participants: Jack Nicholson, Glenn Close, Annette Bening, Pierce Brosnan, Danny DeVito, Martin Short, Sarah Jessica Parker, Michael J. Fox, Rod Steiger, Tom Jones, Lukas Haas, Natalie Portman, Jim Brown,Lisa Marie, Sylvia Sid Sylvia Sidney./ Audience: Rated PG-13
Keywords: Comedy films; Science fiction films